2002
DOI: 10.1007/pl00012425
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of antigen-induced arthritis in guinea pigs by a selective LTB4 receptor antagonist LY293111Na

Abstract: LTB4 but not PGE2 appeared to play important roles as an effective mediator in joint, particularly in cartilage and bone destruction of AIA in guinea pigs probably by inducing polymorphonuclear leukocytes (PMNs) chemotaxis to the joint tissue. In contrast, PGE2 but not LTB4 is an important mediator of arthritis in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…MPO is a specific enzyme of polymorphonuclear leucocytes (PMN) and is released when these cells are stimulated during inflammatory reactions. Increased MPO activity was observed in antigen-induced arthritis in guinea pigs and was attributed to neutrophils attracted to synovial tissue (Kuwabara et al, 2002). It has recently been reported that MPO mRNA levels are increased in osteoarthritic chondrocytes (Attur et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…MPO is a specific enzyme of polymorphonuclear leucocytes (PMN) and is released when these cells are stimulated during inflammatory reactions. Increased MPO activity was observed in antigen-induced arthritis in guinea pigs and was attributed to neutrophils attracted to synovial tissue (Kuwabara et al, 2002). It has recently been reported that MPO mRNA levels are increased in osteoarthritic chondrocytes (Attur et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…This demonstrates that guinea pigs might be a useful animal model in preclinical tests of MPGES1 inhibitors. In addition, guinea pigs have been used to study inflammatory diseases in several models of arthritis, including antigen-induced arthritis (18) and adjuvant-induced arthritis (19, 20). Although guinea pigs and humans share the same amino acid residues in positions 131, 135, and 138 of MPGES1, allowing for species discriminating MPGES1 inhibitors to bind, the overall identity of the two enzymes is only 79%.…”
Section: Discussionmentioning
confidence: 99%
“…In human medicine, MPO has been measured as a marker of neutrophil activation and tissue infiltration in a broad variety of pathologies (Serteyn et al 2003), including OA (Deberg et al 2008). Increased MPO activity was also observed in antigen-induced arthritis in guinea pigs and was attributed to neutrophils that were attracted to synovial tissue (Kuwabara et al 2002).…”
Section: Introductionmentioning
confidence: 97%